Principles of modern chemistry - Oxtoby, David W. (Saunders College Publishing, 1999)
The fourth edition of PRINCIPLES OF MODERN CHEMISTRY, which has dominated the honors and high mainstream general chemistry courses, is a substantial revision that maintains the rigor of previous editions but reflects the exciting modern developments taking place in chemistry today. The text provides a unique approach to learning chemical principles that emphasizes the total scientific process--from observation to application--placing general chemistry into a complete perspective for serious-minded science and engineering students.